Pattern of Congenital Heart Diseases and Treatment Options in a Bangladeshi Centre: Analysis of 6914 cases from Non-invasive Cardiac Laboratory (Cardiovascular Journal, 2017)
Background: Echocardiography is the most sensitive tool to diagnose congenital heart diseases efficiently. It can be repeated as many times as required to see the progress, outcome of treatment and complications. Echocardiography laboratory can give a scenario of pattern of congenital heart diseases existing in Bangladesh as well as natural history of the cases and treatment options offered.Methods: It is a retrospective review of database of echocardiography patient from pediatric noninvasive laboratory of a cardiac hospital from January 2012 to December 2012.Results: Out of 6914 cases 55.73% were male and 44.27% female. Neonates include 8.48%, 36.62% Down Syndrome were infant, 34.02% were under 5 years, 17.97% were children and adolescents and 2.96% were adults. Normal Echocardiography finding was found in 17.28% cases. Ventricular septal defect (VSD) was found in 18.60% cases, Atrial septal defects (ASD) in 15.41% cases, Patent ductus arteriosus (PDA) in 8.59% cases, Atrioventricular septal defect (AVSD) in 1.97% cases, Tetralogy of Fallot (TOF) in 4.79% cases and Transposition of great arteries (TGA) in 2.26% cases. Down syndrome was the commonest chromosomal abnormality seen in 2.4% cases.Conclusion: This study shows that VSD is the commonest congenital heart lesions in our country followed by ASD. Down syndrome was the commonest chromosomal abnormality seen in 2.4% cases.Cardiovasc. j. 2017; 9(2): 97-105